2020
DOI: 10.1002/cae.22363
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of reverse engineering pedagogy in K‐12 robotics education

Abstract: The purpose of the study is to explore the effectiveness of reverse engineering pedagogy (REP) and forward project‐based pedagogy (FPP) in K‐12 robotics education. A two‐stage study was conducted in two secondary schools, involving a total of 169 students. Based on the experience of the pilot study (Study 1), we refined the REP and examined its effectiveness through a quasi‐experimental design in the formal study (Study 2), which included four teaching models: the Deconstruction Recovery Model, Troubleshooting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
(38 reference statements)
4
24
0
Order By: Relevance
“…This study demonstrates that, after reverse engineering activities where students are exposed to the internal structure of a bimetal thermostat, the students were more positive about the use of their creative ideas to overcome the engineering design challenge to prototype their own bimetal thermostat. This result is consistent with Zhong et al's (2020) results, indicating that reverse engineering can even better facilitate students' creative self-efficacy (i.e., how they view their own abilities in creative product development) than forward engineering. In fact, as McLellan and Nicholl (2011) noted, tasks involving product analysis (i.e., a key part of reverse engineering) can be used if and only if they are designed to maintain ambiguity and risks in a balanced way.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study demonstrates that, after reverse engineering activities where students are exposed to the internal structure of a bimetal thermostat, the students were more positive about the use of their creative ideas to overcome the engineering design challenge to prototype their own bimetal thermostat. This result is consistent with Zhong et al's (2020) results, indicating that reverse engineering can even better facilitate students' creative self-efficacy (i.e., how they view their own abilities in creative product development) than forward engineering. In fact, as McLellan and Nicholl (2011) noted, tasks involving product analysis (i.e., a key part of reverse engineering) can be used if and only if they are designed to maintain ambiguity and risks in a balanced way.…”
Section: Discussionsupporting
confidence: 89%
“…Even so, it seems that reverse-engineering activities can enhance students' perceptions about collaboration, as the process encourages them to share ideas, knowledge, and competencies to collaboratively solve an engineering problem. This result also supports Zhong et al (2020), who found that the degree of compatibility within groups of students significantly improved after they had engaged in the process of reverse engineering, which requires them to cooperate and communicate at the beginning when they are trying to figure out how a product functions and works. In contrast to forward engineering activities, in which students can begin with "designing work directly and individually" (Zhong et al, 2020, p. 12), they can have "a conflict with peers in groups that occurred from a dispute about problems or errors and ideas they confronted," especially when "they are not successful in communicating their problem-solving process with others in order to fix the problems" (Chusinkunawut et al, 2020, p. 2).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Chang et al (2019) investigated the effect of using computer-aided design application (3D-CAD) on the CSE of high school students. Zhong et al (2020) investigated the effects of reverse engineering pedagogy and forward-looking project-based pedagogy on the CSE of secondary school students in K-12 robotics education using quasiexperimental design. Lin and Wang (2021) used virtual reality in his EFL classroom to facilitate the CSE and intrinsic motivation of university students.…”
Section: Research Issues/themesmentioning
confidence: 99%